Implementation of PhET Media in the Discovery Learning Model towards Student Learning Outcomes on Reaction Equations Material - Asyrifah Nur Qalby Asyrifah Nur Qalby; Army Auliah; Sugiarti (Universitas Lampung, 2026)
Implementation of PhET Media in the Discovery Learning Model towards Student Learning Outcomes in the Reaction Equations Material. This study aims to determine the significant differences in student learning outcomes before and after using PhET media in the discovery learning model on reaction equations material. The population in this study were students of class X at MA Muhammadiyah Limbung which were divided into two class. The research sample were 22 students of class X.B selected using simple random sampling MA Muhammadiyah Limbung. The instruments used were pre-test and post-test with 20 questions. The research design used a one-group pre-test and post-test. This study was conducted in one meeting and observed by one observer. Normality tests indicated that the data obtained were not normally distributed, so testing was continued with non-parametric statistics, namely the Wilcoxon Signed Rank Test conducted using SPSS, and additional analysis, namely the N Gain Test. The results showed that PhET learning media was effective in improving student learning outcomes with a Sig.value of 0.000<0.05 and N-gain persentage 79.09%.